Fifth Five Year Plan Draft Annual Plan 1974-75 Volume I Government of Bihar - Planning Commission (Planning Commission, 1973)
There were 17.49 million workers of various ..categories in the State in 1971, which worked out to about 31 per cent of the total population. the proportion of workers for the country as a whole worked out to about 33 per cent. This would appear to indicate somewhat heavier burden of dependency in the State than in the country generally. Of the total workers in the State, about 43.35 per cent are cultivators and 38.92 per cent agricultural labourers.
Planning Department Government of Bihar